Pengaruh Penambahan Semen Tipe I Terhadap Nilai Kuat Geser Tanah - Krisna Dwiyana Soehendro; Roma Kusuma; Daniel Hartanto (G-SMART, 2019)
The type of soil that is quite often found in Semarang City is expansive soil. Expansive soil is some types of clay soil which has high value of shrinkage and plasticity. One of the common problem from this charateristic is found at Jalan Taman Verbena, Kelurahan Sadeng, Kecamatan Gunungpati, Semarang. The problem that usually occur are broken walls and cracks, and also bumpy floors. One of the solution that the writer give to increase the value of expansive soil shear strength is to conduct research on adding cement with different percentage as the additiver. In this research, the writer use type I cement with the percentage of 0%, 5%, 10%, 15%, and 20% from the weight of dry soil. The reasearch that the writer do are mineralogi test, index properties test, atterberg limit test, sieve analysis test, standard proctor test, swelling test and direct shear test. Based on the direct shear test, the best value of cohesion was obtained at 10% of cement adding on the soil sample with 28 days of curing with the value 3,75 kg/cm2, while the best value of shear angle was obtained at 20% of cement adding with 28 days of curing with the value 88,00°. The conclusion that the writer can be conclude is cement has good effect in increasing the value of expansive soil shear strength.